2019
DOI: 10.1080/23288604.2018.1543521
|View full text |Cite
|
Sign up to set email alerts
|

Governance Functions to Accelerate Progress toward Universal Health Coverage (UHC) in the Asia-Pacific Region

Abstract: Many countries in the Asia-Pacific region have committed to universal health coverage (UHC), which is reflected in both their political commitment and the governance actions they have taken in steering their health systems toward the goals of universal access to care and protection from financial hardship. Countries throughout the region are at different stages of development and have different political and governance contexts, which in turn shape how they pursue governance for UHC. This article reviews the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…A study from China showed that strengthening health governance significantly improved the health service and health insurance coverage (55). A study by Yeoh et al on the Asia-Pacific region states that fair governance functions to accelerate progress toward UHC (56). A policy research working paper by the World Bank Human Development Network concluded that governance (fair implementation of health program and policy) accelerates health outcomes and increases the health service coverage (57).…”
Section: Discussionmentioning
confidence: 99%
“…A study from China showed that strengthening health governance significantly improved the health service and health insurance coverage (55). A study by Yeoh et al on the Asia-Pacific region states that fair governance functions to accelerate progress toward UHC (56). A policy research working paper by the World Bank Human Development Network concluded that governance (fair implementation of health program and policy) accelerates health outcomes and increases the health service coverage (57).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, services that are necessary such as health care have inelastic market and consumers have little freedom of choice, and if unregulated, they can lead to serious financial catastrophe that will disturb the whole community. [ 4 ]…”
Section: Resultsmentioning
confidence: 99%
“…Most of the costs of medicines in these counties are directly from out of patient's pocket, making medicines the largest family expenditure item after food. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Universal health insurance, a key component of Sustainable Development Goals, is a priority for the Indian government (Mukherjee, 2019;Wenham et al, 2019). Many countries are facing the challenge in implementing universal health programmes due to an overburdened public health care system (Yeoh et al, 2019). Due to increasing out of pocket expenditure on health, health insurance has emerged as a primary health financing mechanism in India (Peters, Yazbeck, Ramana, & Cho, 2018).…”
Section: Discussionmentioning
confidence: 99%